The Relationship Between Legal Status and Housing Cost Burden for Immigrants in the United States. Issue 3 (4th May 2022) - Allen, Ryan
ABSTRACT: In recent decades, the number of unauthorized immigrants in the United States has increased substantially, while simultaneously housing affordability has become a crisis. Despite these trends and the role that immigrant legal status plays in stratifying immigrants over a range of social and economic outcomes, little research focuses on the relationship between immigrant legal status and housing affordability. Using a nationally representative data set and a logical imputation method that estimates immigrant legal status in the data, this article explores the relationship between immigrant legal status and housing cost burden. Results from logit regression models indicate that unauthorized immigrant and mixed legal status renter households are more likely to experience housing cost burden than are households comprised of immigrants living in the United States lawfully or native-born residents, even after controlling for a variety of factors. Among owner households, households of unauthorized and mixed legal status are more likely to experience housing cost burden than are native-born households. As a result, unauthorized immigrants and their families likely experience a disadvantage in the housing market of the United States.